Monitoring in a DevOps World. - SCHLOSSNAGLE, THEO (Communications of the ACM, 2018)
The author discusses the issue of monitoring in software development operations. He mentions the changes in how quickly software is upgraded, the use of machine learning in the monitoring process, and the nature of successful monitoring which includes getting a system in place and then looking for improvements.